Tutela específica e meios coercitivos para o cumprimento das obrigações contratuais: um estudo da jurisprudência do superior tribunal de justiça à luz da literatura de direito e economia - Barreto, Gabriel de Almeida (2019)
There is much debate on the role of contractual law (and legal institutions, in general) to promote safety and certainty for the relations of economic agents. In Brazil, part of the doctrine regards the contractual law as inefficient and weak when called to remedy the breach of contractual commitments, thus creating obstacles to the development of businesses in the country. If, on the one hand, Brazilian law “in books” seems to protect against such breaches, on the other hand it is essential to analyze how law works “in action” to conclude whether, in fact, the commitments are or are not efficiently protected. One of the mechanisms used to enforce breached agreements is precisely the specific performance of contractual obligations. While in common law countries there seems to be no subjective right to this kind of performance, it is the general belief that in civil law countries specific performance is the preferred mean to enforce breached obligations. The main purpose of this work is to map the position of Brazilian Superior Court of Justice (“STJ”) regarding the specific performance of contractual obligations and the coercive means applied to enforce such obligations. Through this map, this work tries to verify to which extent Brazilian law “in action” corresponds to Brazilian law “in books”, joining the debate proposed by part of the doctrine that criticizes the substance of what is being judged by Brazilian Tribunals in contractual matters. In general lines, STJ’s case law seems to follow the law in books, and does not easily allow for the breach of obligations and their conversion into damages. On the other hand, there is a certain tension among members of the Tribunal regarding the possibilities of limitation of the so called astreintes, which can lead to judicial uncertainty. At last, with the innovations provided by the recently enacted New Civil Procedural Code (“Novo CPC”) the Tribunal has been authorizing the application of more severe atypical coercive means, which consequences can only be observed in the medium and long run.